Lebih dari Sekadar Lelah: Dinamika Parental Burnout, Kekerasan, dan Ide Bunuh Diri pada Ibu Tunggal Buruh Desa KA - Diana Putri Arini; Hikmah (Journal of Psychology and Social Sciences, 2026)
Parental burnout is a chronic exhaustion resulting from stress parenting. Single mothers from rural low-income background, bearing dual roles and limited resources, are highly vulnerable to this condition with more complex manifestations. This study aims to explore in depth experiences, dynamic and impacts of parental burnout among single mothers working as laborer in KA Village. This qualitative study with phenomenological approach involved three single mother laborer participants selected via purposive sampling. Data were collected through in depth interviews and observation, the analyzed using Interpretative Phenomenological Analysis (IPA). The findings revealed that all three participants experienced parental burnout, fulfilling all four dimensions: exhaustion (extreme fatigue with physical impact), emotional distancing (emotional detachment from children), ineffectiveness in the parental role (feeling of failure as a parent), and feelings of being fed up. The emerging impacts were more severe than the general portrayal of parental burnout, including tendencies toward neglect, verbal and physical violence against children, as well as suicidal ideation and the desire to escape. This study expands the understanding of parental burnout by demonstrating more severe manifestations and a higher degree of intensity among rural low-income single mothers with extremely limited personal and social resources. These findings indicate the urgency of contextual psychosocial interventions for this vulnerable group.